(3GdJfXje GdbGfhfi dJTZjd Phi GdGMJjGLGJ GdNGUI hMeGjJge (B: s (3OQGSI ebGQfI (B/ s - (3YHOGdEdg RHjQGJ s; (3GMeO MSf GdHQYi (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s, 2010)
(3MGhdJ gPg GdQSGdI GdJWQb Gdi ehVhY GdJfXje GdbGfhfi dJTZjd hMeGjI Phi GdGMJjGLGJ GdNGUI ef GdeYGbjf MjK JfGhd eGgjI GdGYGbI hfXQI GdTQjYI GdGSdGejI GdjgG hGfhGY hMLe eTcdI GdGYGbI hGdJfXje GdbGfhfi dGdJMGb GdeYGb HGdYed hGdJCgjd Gdegfi ddeYGbjjf hGdMeGjI GdbGfhfjI ddYeGd GdeYGbjf hMeGjI GdYGed GdeYGb ai bGfhf GdYed ai Mjf JWQb GjVG ddMeGjI GdebQQI ai GdJCejfGJ GdGLJeGYjI s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdJTQjYGJ GdGLJeGYjI (B2010s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdJTQjYGJ GdELJeGYjIs; (3GfhGY hMLe eTcdI GdGYGbI s; (3JCgjd hJOQjH GdGTNGU GdeYGbjf s; (3fXQI GdTQjYI GdGSdGejI ddGTNGU GdeYGbjf s; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQI s -- (3cdjI GdMbhbs